Opinion mining and sentiment analysis in marketing communications: a science mapping analysis in Web of Science (1998–2018) - Sánchez-Núñez, Pablo; De-las-Heras-Pedrosa, Carlos; Peláez-Sánchez, José Ignacio (MDPI, 2020)
Opinion mining and sentiment analysis has become ubiquitous in our society, with applications in online searching, computer vision, image understanding, artificial intelligence and marketing communications (MarCom). Within this context, opinion mining and sentiment analysis in marketing communications (OMSAMC) has a strong role in the development of the field by allowing us to understand whether people are satisfied or dissatisfied with our service or product in order to subsequently analyze the strengths and weaknesses of those consumer experiences. To the best of our knowledge, there is no science mapping analysis covering the research about opinion mining and sentiment analysis in the MarCom ecosystem. In this study, we perform a science mapping analysis on the OMSAMC research, in order to provide an overview of the scientific work during the last two decades in this interdisciplinary area and to show trends that could be the basis for future developments in the field. This study was carried out using VOSviewer, CitNetExplorer and InCites based on results from Web of Science (WoS). The results of this analysis show the evolution of the field, by highlighting the most notable authors, institutions, keywords, publications, countries, categories and journals.
Keywords: Bibliometría; Sentiment analysis; Opinion mining; Marketing; Communication; Science mapping analysis; Web of Science (WoS); Bibliometric indicators; Scientific collaboration